Challenge of Reconstructive Surgery of the Eyelids - Nenad Tanasković; Miroslav Obrenović (Биомедицинска истраживања, 2010)
Introduction: In eyelid as well as the face reconstruction, besides functional, it is significant to respect aesthetic aspects as well. In this paper the results of eyelid reconstruction in 42 patients with malign tumour of the eyelid skin are shown. Methods: In all patients within preoperative preparation CT and/or MRI were carried out depending on consultative decision of maxillofacial surgeon and radiologist, as well as exploration of lacrimal system. In eyelid reconstruction, transpositional flaps were used according to Lagebek and Tripier, frontal flaps according to Mustard, skin graft and mucousal transplants. Results: On the basis of frequency of postoperative complications, functional results and the degree of satisfaction with postoperative appearance, the best results were found in elderly patients since elasticity of their eyelids is decreased, therefore their mobilisation is easier. In two patients the use of skin grafts caused the development of ectropion, and distant metastases in two other patients. Eyelid reconstruction in patients with malignant skin tumours cannot be performed with simple skin transplants in most cases, and it is not possible to correct the defect with direct suture if it is larger than the third of the eyelid dimension. For defects expanding these measures it is necessary to perform cantholysis because of relaxation of eyelid tissue and to use local flaps. However, none of the local flaps is ideal for the reconstruction of eyelid edge. Conclusion: Eyelid reconstruction requires individual planning which depends on many factors, out of which the size of defect and the age of patients are especially significant. In planning of this reconstruction, an individual character of their vascularisation should be taken into consideration, which can be significant for development of complications and the result of surgical reconstruction.
Keywords: eyelid; reconstruction; aesthetics; malignant tumours